The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41417-021-00360-2
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus mutant jin-3 exhibits lytic and immune-stimulatory effects in preclinical human prostate cancer models

Abstract: Treatment of castration-resistant prostate cancer remains a challenging clinical problem. Despite the promising effects of immunotherapy in other solid cancers, prostate cancer has remained largely unresponsive. Oncolytic viruses represent a promising therapeutic avenue, as oncolytic virus treatment combines tumour cell lysis with activation of the immune system and mounting of effective anti-tumour responses. Mammalian Orthoreoviruses are non-pathogenic human viruses with a preference of lytic replication in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“… 53 , 77 , 78 , 79 , 80 For RV jin-3, hallmarks of ICD were found after treatment of patient-derived prostate cancer models. 81 …”
Section: Discussionmentioning
confidence: 99%
“… 53 , 77 , 78 , 79 , 80 For RV jin-3, hallmarks of ICD were found after treatment of patient-derived prostate cancer models. 81 …”
Section: Discussionmentioning
confidence: 99%
“…In the session’s final talk, Dr. van de Merbel gave an overview of “Patient-derived tumor models for personalized therapeutics in prostate cancer.” Using her data on the oncolytic virus jin-3 reovirus, she described the advantages and pitfalls of PCa models such as syngeneic mice models, 3D prostate organoids, ex vivo slices, and patient-derived xenografts [ 61 , 62 ]. She revealed that oncolytic viruses are powerful in stimulating antitumor immune responses and may potentiate immunotherapy.…”
Section: Session 2: New Advances From Basic and Translational Researchmentioning
confidence: 99%
“…Preclinical studies of reovirus against PCa were conducted later than those of Ads. In 2010, Morris et al found that reovirus caused the death of human prostate cancer cells PC-3, LNCaP and Du-145 by apoptosis, and tumor reduction was observed after a single intratumoral injection of the virus in nude mice bearing human prostate cancer xenografts [ 193 ]. Wild-type reovirus binds to cancer cells through the interaction of the viral stinger protein Sigma-1 with sialic acid and junctional adhesion molecule A (JAM-A).…”
Section: Oncolytic Virotherapy For Pcamentioning
confidence: 99%